Pengaruh Sertifikasi Guru, Kompetensi Profesional, dan Pengembangan Karir Terhadap Kinerja Guru - Ramli, Ramli; Sihombing, Ankus; Suzanna, Nana; Zuhra, Cut Elviana; Lubis, Hasrita; Wasesa, Supar; Supriadi, Supriadi (Journal of Management and Economics Research, 2024)
This study aims to determine the influence of teachers’ certification, professional competence, and career development on teachers’ performance at SMP Negeri 1 Peureulak. This study uses a quantitative approach, while the research technique is carried out by distributing questionnaires to research respondents, totaling 59 teachers at SMP Negeri 1 Peureulak. The results showed that there was a positive and significant effect between teachers’ certification on teachers’ performance at SMP Negeri 1 Peureulak. This is evidenced by the value of the coefficient tcount < ttable, which is 2,951 > 1.672 at a significant value of 0.005 < 0.05. It is concluded that the research hypothesis H0 is rejected and H1 is accepted. There is a positive but not significant effect among professional competence on teachers’ performance at SMP Negeri 1 Peureulak. This is evidenced by the value of the coefficient tcount > ttable, which is 0.206 < 1.672 at a significance level of 0.838 > 0.05. It is concluded that the research hypothesis H₀ is accepted and H2 is rejected. There is a positive and significant influence among career development on teachers’ performance at SMP Negeri 1 Peureulak. This is evidenced by the value of the coefficient tcount > ttable, which is 0.206 < 1.672 at a significance level of 0.838 > 0.05. It is concluded that the research hypothesis H₀ is rejected and H3 is accepted. There is a simultaneous positive influence between teachers’ certification, professional competence, and career development on teachers’ performance at SMP Negeri 1 Peureulak. Based on the results of the F test, it can be seen that the variables consisting of teachers’ certification (X1), professional competence (X2), career development (X3), have a significant value of 0.000 < 0.05 and the value of Fcount > Ftable (48.869 > 3.15). Thus the decision is obtained that H0 is rejected and H4 is accepted. In addition, the multiple linear regression models in this study are feasible to use because it has a positive value. The magnitude of the coefficient of determination (R Square) is R Square 0.727 or equal to 72.7%. This figure means that the variables of teachers’ certification, professional competence, career development, simultaneously (together) affect teachers’ performance by 72.7%. While the rest is 100% - 72.7% = 27.3%. This means that 27.3% is influenced by other variables outside the regression equation or the variables studied.